Beyond nostalgia: Other historical emotions. Issue 3 (27th May 2019) - Gilbert, Andrew
ABSTRACT: A disproportionate focus on nostalgia in post-socialist societies has resulted in analytic limits to our ability to account for diverse uses of the past. I argue that the concepts of chronotope, voice, and participation framework, when combined with the nostalgia scholarship's attention to the role of emotion and affect in semiosis, can move us beyond these limits. The resulting analytic framework will be of value to anthropologists interested in the relationship between historical consciousness, social action, and cultural production.